Construction and Reconstruction of the 'Other' - School History Education and Post-War Reconciliation in Sri Lanka - Korala, Anjali (University of Colombo, 2015)
The practice of utilizing the national education system itself as a tool for reconciliation has a relatively short history, but this has not relegated its importance in the reconciliation processes. From the dawn of the twentieth century, the significance of educating future generations about the historical myths which brought about social conflicts, and instilling mutual acceptance between former hostile social groups have gradually come to constitute a core area in reconciliation processes which aim for just and long- lasting peace. Although the international community has accentuated the contribution education can make to reconciliation, Sri Lanka, having experienced a war for nearly three decades, does not seem to have grasped its importance. The history text books in post-independent Sri Lanka continued to feature racist and historically skeptical details that were in line with the existing regime's political aspirations. Therefore, even before the word 'reconciliation' with a conceptual base is absorbed by the Sri Lankan society, since May 2009, numerous academics have stressed the impact an iniquitous education system can make upon the mutual coexistence of the Sinhalese and Tamils. This paper points out how the present local history text books have been instrumental in constructing, reconstructing and regenerating the prolonged 'Sinhalese historical consciousness' about the Tamil 'other' among the younger generation, and how Sri Lankan school syllabus reviewers have largely ignored the internationally accepted guidelines in text book review and analysis. It also focuses on how this iniquitous education system hinders Sri Lanka's achievement of 'positive co-existence' in post-war Sri Lanka. The paper was developed based on findings of a research conducted for my Bachelor's degree, in Political Science. A desk research was conducted based on history textbooks and other relevant theoretical materials. The analysis transpired two major implications: (a) the prevailing history syllabus presents an unbalanced history to the younger generation; (b) the history text books strongly confirmed and supported a Sinhalese group identity while differentiating the Tamils as an alien social group with no legitimate right to the land. These results emphasize the importance of the government's responsibility in re-examining and reviewing the history text books, in its quest for reconciliation.
Keywords: Reconciliation, Text book analysis, Ethnic conflict, Coexistence, Other